2010
DOI: 10.1097/jcn.0b013e3181cfbb88
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters in Men and Women With Heart Failure and Their Impact on Cardiac Event-Free Survival

Abstract: Although distress for individual symptoms may differ between men and women, they both experienced identical symptom clusters. Only the emotional/cognitive cluster predicted a higher risk for a cardiac event. These results suggested that interventions should be developed that consider symptom clusters. Targeting patients who have high distress from emotional/cognitive symptoms may be particularly important as they may be most vulnerable for adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
126
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(149 citation statements)
references
References 54 publications
(41 reference statements)
11
126
0
9
Order By: Relevance
“…This claim is supported by significant relationships among the variables studied (symptoms), with correlation coefficients ranging from r = -0.3 (fatigue and sleep disturbance) to 0.8 (anxiety and depression) at p \ 0.05, warranting further investigation. In symptom cluster studies involving moderate to advanced HF patients, investigators found that anxiety (worrying) and depression are clustered within emotional/cognitive symptoms whereas fatigue and sleep disturbance clustered as physical symptoms [20,21]. Thus, our results support the need for more symptom-cluster research in HF and mechanical circulatory support.…”
Section: Discussionsupporting
confidence: 83%
“…This claim is supported by significant relationships among the variables studied (symptoms), with correlation coefficients ranging from r = -0.3 (fatigue and sleep disturbance) to 0.8 (anxiety and depression) at p \ 0.05, warranting further investigation. In symptom cluster studies involving moderate to advanced HF patients, investigators found that anxiety (worrying) and depression are clustered within emotional/cognitive symptoms whereas fatigue and sleep disturbance clustered as physical symptoms [20,21]. Thus, our results support the need for more symptom-cluster research in HF and mechanical circulatory support.…”
Section: Discussionsupporting
confidence: 83%
“…With patient or family assistance, hospital discharge and other medical records were obtained from identified sources of care outside of the study‐site healthcare systems. We have >20 years of experience collecting these data and have successfully obtained hospitalization data on all rural patients in our current and previous studies 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41. All‐cause mortality data (date and cause of death) were collected for 1 year from baseline by a combination of medical record review, electronic clinical record review, interviews with patients’ healthcare providers and family, and public death record review 30, 31, 40, 41, 42, 43…”
Section: Methodsmentioning
confidence: 99%
“…Studies have suggested that the occurrence of multiple symptoms frequently leads to the occurrence of symptom clusters 51 . These symptom clusters might be more important to explore rather than individual symptoms, especially when it comes to determining the impact on outcomes 52,53 .…”
Section: Limitationsmentioning
confidence: 99%